PENGARUH RASIO PERPUTARAN ASET LANCAR DAN RASIO PERPUTARAN TOTAL ASET TERHADAP RETURN ON ASSET PADA KOPERASI SIMPAN PINJAM KOPDIT CU PARDOMUAN PAKKAT CABANG PANDAN KABUPATEN TAPANULI TENGAH - Rahmi Ayuni Sianturi; Zafril Abdi Nasution; Mansur Tanjung (LPPM Universitas Deli Sumatera, 2024)
The aim of this research is to determine the effect of the current asset turnover ratio and total asset turnover ratio on return on assets at Koperas Savings and Loans Kopdit CU. Pardomuan Pakkat Pandan Branch, Central Tapanuli Regency draws the hypothesis that there is an influence of the current asset turnover ratio and total asset turnover ratio on return on assets in the Kopdit CU Savings and Loans Cooperative. Pardomuan Pakkat Pandan Branch, Central Tapanuli Regency. The results of the research show that there is a positive relationship between the current asset turnover ratio and return on assets and the total asset turnover ratio and return on assets have a positive relationship in the Kopdit CU Savings and Loans Cooperative. Pardomuan Pakkat Pandan Branch, Central Tapanuli Regency is 0.447 and 0.249 respectively, so that when interpreted on a value scale it can be categorized as moderately positive and low positive. The regression equation obtained is Y = 0.075 + 0.008X1 - 0.007X2 which shows the influence of the current asset turnover ratio and total asset turnover ratio on return on assets. The t test shows that the hypothesis proposed is rejected as true, where the t count is 0.612 < 3.18245 for the current asset turnover ratio and the t count is -0.160 > -3.18245 for the total asset turnover ratio, where both ratios have a positive and negative effect on return on assets are not significant, which means they will not necessarily increase or decrease by the respective regression coefficient/slop of 0.008 and -0.007 if the current asset turnover ratio and total asset turnover ratio variables are increased by one unit. Meanwhile, the coefficient of determination shows that the current asset turnover ratio and total asset turnover ratio only play a role of 21% in the return on assets at the Kopdit CU Savings and Loans Cooperative. Pardomuan Pakkat Pandan Branch, Central Tapanuli Regency and the remaining 79% is influenced by other factors not included in the model. Keywords: Current asset turnover ratio, total asset turnover ratio and return on assets